Principles of Entrepreneurship (ENT530): Business Model Canvas: Dapo Kak Az / Amirul Affiq Amran ... [et al.] - Amran, Amirul Affiq; Ali, Azlina; Ali, Nurdiyana; Alias, Siti Nursyahirah (2020)
‘Dapo Kak Az’ offers superior café design, comfortable and affordable foods and drinks for all generation of age. We will provide various types of ‘tauhu bergedil’ (healthy snacks) that mouthwatering and fulfilled customer needs. ‘Dapo Kak Az’ is a business that will make people feel relax while enjoying their food.